Responsibility of Transportation Business Actors for Passenger Losses from a Maslahah Perspective (Case Study of PT. Barumun, Padang Lawas) - M. Syafii Nasution; Muhammad Amar Adly (Dinasti Research, 2024)
One of the barometers determining the progress of life and civilization of a society is the progress and development of information and technology activities used by the community in transportation activities. This study aims to determine the losses suffered by passengers due to the negligence of the bus company and the liability of transportation business actors for passenger losses with a focus on the Maslahah perspective. The research used is empirical juridical research with a Living Case Studies Approach and Conceptual Approach. Data is collected by interview and document study methods. Then the data is processed and analyzed with qualitative methods. The results of this study indicate that the responsibility of PT Barumun for the operation of buses that cause losses to passengers in terms of security, comfort, and safety of passengers and their luggage. In the maslahah perspective, the bus company's responsibility for passengers who suffer losses can be done by replacing all losses arising from the operation of the bus in accordance with applicable regulations so as to create benefits for all passengers who want to travel short or long distances by using PT. Barumun bus services.